2009
DOI: 10.1007/s10295-009-0630-z
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a purified thermostable glucoamylase from Aspergillus niveus

Abstract: A glucoamylase from Aspergillus niveus was produced by submerged fermentation in Khanna medium, initial pH 6.5 for 72 h, at 40 degrees C. The enzyme was purified by DEAE-Fractogel and Concanavalin A-Sepharose chromatography. The enzyme showed 11% carbohydrate content, an isoelectric point of 3.8 and a molecular mass of 77 and 76 kDa estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis or Bio-Sil-Sec-400 gel filtration, respectively. The pH optimum was 5.0-5.5, and the enzyme remained stable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
2
28
0
2
Order By: Relevance
“…Earlier studies have shown that the addition of various metal ions and chemicals can have a positive effect on hydrolytic [34][35][36]. Here, we questioned whether the application of select ions or chelators at two different concentrations (2.5 and 5 mM) could enhance the activity of Ayt40 and Ayt70 (Fig.…”
Section: Impact Of Mn 2+ Amendment On Trichoderma J113 Amylase Activitymentioning
confidence: 88%
“…Earlier studies have shown that the addition of various metal ions and chemicals can have a positive effect on hydrolytic [34][35][36]. Here, we questioned whether the application of select ions or chelators at two different concentrations (2.5 and 5 mM) could enhance the activity of Ayt40 and Ayt70 (Fig.…”
Section: Impact Of Mn 2+ Amendment On Trichoderma J113 Amylase Activitymentioning
confidence: 88%
“…One sector that has been widely economically explored is the application of amylases in processes of starch saccharification (Silva et al, 2009a(Silva et al, , 2009b. For so, there is the need of several enzymes such as -amylase, which forms maltooligosaccharides; glucoamylases and -amylases, which hydrolyze starch to glucose and maltose and the glucosyltransferases with the production of cyclodextrins.…”
Section: Some Industrial Enzymes and Their Applicationsmentioning
confidence: 99%
“…Fig. 2A illustrates the activity of -glucosidase, one of the enzymes of the amylolytic system, which leads to the formation of glucose as end product (Aquino et al, 2001;Silva et al, 2009aSilva et al, , 2009b.…”
Section: Amylasementioning
confidence: 99%
“…The reaction mixture was dissolved in 50 μl sodium phosphate buffer (pH 5.5). Fifty mUnit of Endoglycosidase H (Genzyme, Cambridge, MA) was added to the reaction mixture and incubated at 37 o C for 24 hr followed by 9% SDS-PAGE analysis [2]. Effect of temperature on enzyme activity…”
Section: Con-a Sepharose Chromatographymentioning
confidence: 99%